Introducing two New Methods for Factorization Natural Odd Numbers - Ramazanali Maleki Chorei (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
For each non-prime odd number as F=pq, if we consider m/n as an approximation for q/p and choose k=mn, then by proving some lemmas and theorems, we can compute the values of m and n. Finally, by using Fermat’s factorization method for F and 4kF as difference of two non-consecutive natural numbers, we should be able to find the values of p and q. Then we introduce two new and powerful methods for separating composite numbers from prime numbers.